Systematics of the Relhaniinae (Asteraceae-Gnaphalieae) in southern Africa : geography and evolution in an endemic Cape plant lineage - Bergh, Nicola Georgina (Department of Biological Sciences, 2014)
Includes bibliographical references (p. 161-194).